Through the integration to the regulated market of fresh vegetables in Slovenia (Journal of Universal Excellence, 2026)
Research Question (RQ): Disconnectedness of Slovenian producers is reflected in a markedly disadvantageous position in purchasing and sales marketing. Therefore, we raised a research question about the possibilities for the creation of an optimal model for the integration of producers.Purpose: The purpose of the study is to determine the readiness of stakeholders in the chain of vegetable production for mutual cooperation. The aim of the research is to find the optimal model of vegetable producers' integration and/with other stakeholders.Method: We have come to the results through different research tools. We have analyzed questionnaires with MS Excel and Statgraphyc plus 4.0, having errected an organization model for the integration of growers through a system analysis, comparative analysis and with multicriterion decision-making method DEXi. We have verified these results by applying a method of participatory research.Results: We found in this research that primarily larger agricultural holdings, which produce vegetables, wish to cooperate more intensively with each other. Using the research tools, we have determined the optimal form of mutual cooperation between producers. It is an economic cluster. However, gradual organizing via an producer organization, in particular due to the financial support of the EU, is reasonable.Organization: Competitive advantages acquired as the result of interconnection of growers will be felt on any agricultural holding.Society: By improving the conditions for the marketing of vegetables, self-sufficiency in vegetables will also grow, which will undoubtedly increase the autonomy of society and its independence from food imports from elsewhere.Originality: The study has made an innovative approach to the organization of the optimal model of the integration of vegetable growers. Limitations/Future Research: The study is limited to the vegetable sector, for the other sectors a new study should be carried out.
Keywords: vegetable production; integration of producers; model of integration; economic cluster; produces organization